Analysis of some factors reducing the efficiency and effectiveness of dental accompanying therapy in cancer patients - A. M. Avanesov; E. N. Gvozdikova; E. F. Khalil; E. Yu. Kandakova; K. A. Avanesov (Опухоли головы и шеи)
Introduction. One of the areas of maintenance therapy in oncology is dental support for patients, the effectiveness of which is currently low. The prevalence of complications of anticancer treatment reaches 100 % of cases. This negatively affects the prognosis of the treatment of an oncological patient and the quality of his life.Aim. To analyze the factors that reduce the effectiveness and efficiency of accompanying dental therapy.Materials and methods. Retrospective analysis of clinical observations of the Department of General and Clinical Dentistry named after V.S. Dmitrieva was carried out on the basis of the Russian Scientific Center of Roentgenoradiology.Results. Factors decreasing the quality and effectiveness of accompanying dental therapy are dental unpreparedness of patients prescribed antitumor treatment, very low level of personal hygiene of the oral cavity, as well as insufficient number of available highly effective techniques for treatment and prevention of radiation injuries.Absence of professionals having skills in dental care for oncological patients at all stages of routing (from diagnosis to rehabilitation after completion of antitumor treatment) is another factor contributing to low effectiveness of accompanying therapy and, in our opinion, the most significant. The current clinical guidelines governing the process of examination and treatment of patients with malignant tumors do not contain detailed instructions for dentists about the techniques, approaches of dental accompaniment, and the necessary medications.Conclusion. Factors that reduce the effectiveness and efficiency of dental accompanying therapy have been identified: the lack of trained dental personnel with the skills to provide care to cancer patients; underestimation of the role of a dentist in solving general clinical problems; lack of a systematic approach to providing accompanying therapy to cancer patients; lack of continuity between the polyclinic link and the stationary.